Thermophysical Properties of Complex Materials - Shahzad, Aamir (IntechOpen, 2020)
This book assists in the exchange of research and progress outcomes concerned with the latest issues in thermophysical properties (TPPs) of complex liquids research, development, and production. Topics cover the control of transport properties of metallic alloys, thermal analysis of complex plasmas and instabilities in plasma devices, thermophysical properties at nanolevel, theoretical background of viscosities of hydrocarbons at varying temperature and pressure ranges, molecular modeling, and experimental investigations based on nanofluids and ionic conduction in solid-state electrolytes for thermodynamic data. This book enables global researchers to tackle the challenges that continue to generate cost-effective TPPs and the latest understanding in the development of complex materials and the collaboration of modern thermophysical generating technologies. Moreover, it provides a platform for different regional authors to exchange scientific knowledge and generate enthusiasm for science and technology.